MAKALAH ABDIMAS PSIKOEDUKASI MOTHER ENGAGEMENT UNTUK MEMOTIVASI BELAJAR BAGI ANAK PRA-SEKOLAH DI DUSUN TEGALBEDUG, LELEA, INDRAMAYU - Agoes Dariyo (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Tarumanagara, 2026)
Until now, parents in the village of Tegal Bedug, Lelea, Indramayu, West Java, have been relatively unconcerned about their children's education at school, as they are focused on working to meet their families' economic needs. They tend not to be involved in their children's education. As a result, the children are unable to achieve their best academic performance at school. This situation is very concerning to the head of the Tegal-Bedug village, who hopes that the younger generation will continue their education to the highest level possible so that they can advance the community in the future. This background is the basis for the implementation of a Community Service Program (PKM) entitled Psychoeducation on Mother Engagement to Build Children's Motivation to Learn in Preschool Education. The activity involved mothers who have children studying in preschool education institutions. Those involved in this PKM were coordinated by kindergarten teachers in Tegal Bedug Hamlet, Lelea, Indramayu, West Java. The PKM activity used a pre-test and post-test one group approach. All participants were given questionnaires before and after the activity. Data collection techniques used learning motivation questionnaires for children. Questionnaires were administered before the activity (pre-test) and after the activity (post-test). Data analysis techniques used difference tests, namely t-tests. The analysis results showed that there was a difference between the pre-test and post-test results. The post-test (18.3) results were higher than the pre-test results (15.3). This means that after participating in psychoeducation on mother involvement, mothers were able to increase their efforts to motivate their preschool children to learn. Selama ini, kondisi orangtua masyarakat dusun Tegal Bedug, Lelea, Indramayu, Jawa Barat, tergolong kurang peduli terhadap pendidikan anak-anak di sekolah, karena mereka terfokus untuk bekerja guna memenuhi kebutuhan ekonomi keluarga. Mereka cenderung tidak terlibat dalam pendidikan anak-anaknya. Akibatnya, anak-anak pun tidak mampu mencapai prestasi belajar terbaik di sekolahnya. Hal ini, sangat mencemaskan kepala dusun Tegal-Bedug, dan berharap mereka sebagai generasi muda dapat melanjutkan pendidikan setinggi-tingginya, sehingga mereka dapat memajukan masyarakat di masa mendatang. Latar-belakang inilah yang mendasari pelaksanaan pengabdian kepada Masyarakat (PKM) yang berjudul Psikoedukasi Mother Engagement untuk Membangun Motivasi Belajar Anak di Pendidikan Pra-Sekolah. Kegiatan melibatkan para ibu yang memiliki anak yang sedang belajar di lembaga pendidikan Pra-sekolah. Mereka yang terlibat dalam PKM ini telah dikoordinasi oleh guru-guru Taman Kanak-kanak di Dusun Tegal Bedug, Lelea, Indramayu, Jawa Barat. Kegiatan PKM menggunakan pendekatan pre-test and post-test one group. Semua peserta diberikan kuesioner sebelum kegiatan berlangsung maupun sesudah kegiatan. Teknik pengambilan data dengan menggunakan kuesioner motivasi belajar anak. Pemberian kuesioner dilakukan pada saat sebelum kegiatan (Pre-test) dan dilakukan juga pada saat sesudah kegiatan (Post-test). Teknik analisis data dengan menggunakan uji beda yaitu t-test. Hasil analisis menunjukkan bahwa ada perbedaan antara hasil pre-test dengan hasil post-test. Hasil pre-test (15,3) < hasil post-test (18,3). Artinya setelah mengikuti psikoedukasi mother involvement mampu meningkatkan upaya ibu untuk memotivasi belajar bagi anak pra-sekolah.